Implementation of Sharia Principles in Murabahah Contracts at KCP Bank Muamalat - Hari Subakti; Nurul Jannah (Review of Islamic Economics and Finance, 2022)
Purpose – The purpose of this research is to educate the form of contract used by Bank Muamalat KCP Kisaran. Specifically examining how the application of sharia principles to murabah financing contracts at Bank Muamalat KCP Kisaran.Methodology - This research method is qualitative by processing data from sources of documentation, interviews, field observations, and literature which is carried out by descriptive analysis.Findings - This study has the result that the form of the murabahah financing product contract at Bank Muamalat KCP Kisaran is based on the provisions of the Sharia Banking Law, Bank Indonesia, and the DSN-MUI Fatwa. Then, in the murabahah financing contract at Bank Muamalat Kota Kisaran, sharia principles are applied, including the absence of usury elements, no maisir, garar, haram, and unjust elements.Keywords: Murabahah Agreement, Bank Muammalat, Financing Products